A Measles Outbreak in the Tel Aviv District, Israel, 2018–2019. (3rd July 2020) - Salama, Matanelle; Indenbaum, Vicki; Nuss, Naama; Savion, Michal; Mor, Zohar; Amitai, Ziva; Yoabob, Irina; Sheffer, Rivka
Abstract: During a national measles outbreak in 2018–2019, the Tel Aviv District suffered a major upsurge of cases, with 413 patients reported. Among them, 100 (24%) were <1 year, 92 (22%) patients were aged 12 months to 4 years, 47 (11%) were 5–18 years, 169 (41%) were 19–60 years, and 5 (1%) patients were older than 61 years (born before 1957). Among all cases, 230 (56%) were part of the Ultra-Orthodox Jewish community, 55 (13%) were among undocumented African immigrants. Despite high vaccination coverage, sustained measles transmission occurred, due in part to importations and numerous exposures in medical settings by a susceptible birth cohort. The Ultra-Orthodox Jewish community was particularly afflicted due to its condense population, high birth rates, and multiple exposures in crowded religious settings. This outbreak demonstrates the necessity of addressing immunity gaps as well optimal healthcare planning in order to prevent future outbreaks. Abstract : The Tel Aviv District suffered a measles outbreak in 2018–2019, with 413 patients reported, notably among the Ultra-Orthodox Jewish community. This outbreak demonstrates the necessity of addressing immunity gaps and optimal healthcare planning in order to prevent future outbreaks.